The Kurd Issue in the Middle East - Justyna Misiągiewicz (Facta Simonidis, 2013)
This article surveys the developing situation of Kurdish minority in the Middle East and tries to predict the future of this ethnic group. The emergence of Kurd nationalism is gaining importance nowadays as a challenge for the stability and unity of the states in the region. The Kurdish question is not only connected with the political identity of the Kurds and their willingness to create their own state, but also with their economic weakness and poverty which has caused a violent ethnic conflict between government forces and the Kurdistan Workers Party in Turkey. This paper is aimed at better understanding and analysis of the Kurdish issue in Turkey, Iraq, Syria and Iran, which are Kurds’ homelands in the Middle East.